The sunday blues, Say goodbye to school worries! - LAYTON , NEAL (Hodder children's books, London, 2020)
The Sunday Blues: Say Good-Bye to Back to School Worries! by Neal Layton. This book is designed to help children manage and overcome the anxiety often associated with returning to school after a break. It offers practical advice and strategies to ease the transition and build confidence.